Alkaloids and bioactivity of Papaver dubium subsp dubium and P.dubium subsp laevigatum - (:unkn) unknown (HARWOOD ACAD PUBL GMBH, 2000)
Alkaloids and cytotoxic activity of two samples of Papaver dubium subsp. dubium and one sample of P.dubium subsp, laevigatum have been investigated. Berberine (1), thalifendine (2), corydine (3) and isocorydine (4) have been isolated from the first sample of P.dubium subsp. dubium. The second sample of this species yielded berberine (1), thalifendine (2), isocorydine (4), stylopine (5) and tetrahydropseudocoptisine (6) which was isolated for the first time as a natural product. The existence of roemerine (8), mecambrine (9) and allocryptopine (10) has been shown in P.dubium subsp.laevigatum. The tertiary extract of the latter showed high cytotoxicity.
Keywords: Papaver dubium subsp dubium; Papaver dubium subsp laevigatum; alkaloids